The Influence of Organizational Resources, Organizational Engagement Climate and Job Resources on Employee Engagement Generation Y in Tangerang - Yudistiranda Satya; Yudi Nur Supriadi; Iwan Kresna Setiadi; Desmintari Desmintari (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to analyze regarding the making of employee engagement (EE) in the Tangerang area which is predicted by organizational resources (OR), organizational engagement climate (OEC), and job resources (JR). This research method uses quantitative methods with a sample of 200 respondents from Generation Y employees in Tangerang who have a range of years of birth from 1988 to 1998 and have a minimum service period of 3 months at the current company. The analytical technique used is descriptive analysis and inferential analysis using Smart PLS 3 software. The results of this study indicate that OR has a positive and significant effect on OEC in Generation Y in the Tangerang area. OR has a positive and significant effect on JR in Generation Y in the Tangerang area. OR has a positive and significant effect on EE in Generation Y in the Tangerang area. OEC has a positive and significant effect on EE in Generation Y in the Tangerang area. JR has a positive and significant effect on EE in Generation Y in the Tangerang area. OR has a positive and significant direct effect on EE without having to be mediated by OEC and JR. Keywords : Organizational Resources, Organizational Engagement Climate, Job Resources, Gen Y, Milenial, Tangerang